2019
DOI: 10.3390/genes10110923
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Recapitulates Ovarian Proteins Relevant to Puberty and Fertility in Brahman Heifers (Bos indicus L.)

Abstract: High fertility and early puberty in Bos indicus heifers are desirable and genetically correlated traits in beef production. The hypothalamus–pituitary–ovarian (HPO) axis synthesizes steroid hormones, which contribute to the shift from the pre-pubertal state into the post-pubertal state and influence subsequent fertility. Understanding variations in abundance of proteins that govern steroid synthesis and ovarian signaling pathways remains crucial to understanding puberty and fertility. We used whole ovaries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 169 publications
0
9
0
Order By: Relevance
“…The goal of this pilot study was to develop and characterize a hydrogel derived from decellularized bovine ovarian extracellular matrix (oECM) to support survival and development of isolated human follicles when it was combined with alginate. Bovine ovaries were chosen due to their similarity to human ovaries in terms of ultrastructure, follicle dynamics, rigidity, ECM organization, and composition [31][32][33][34][35][36] and unlimited supply, since they are normally discarded. Furthermore, some bovine-ECM products have already been commercialized 28 and reportedly used without any safety issues which is promising for extending possible clinical applications.…”
mentioning
confidence: 99%
“…The goal of this pilot study was to develop and characterize a hydrogel derived from decellularized bovine ovarian extracellular matrix (oECM) to support survival and development of isolated human follicles when it was combined with alginate. Bovine ovaries were chosen due to their similarity to human ovaries in terms of ultrastructure, follicle dynamics, rigidity, ECM organization, and composition [31][32][33][34][35][36] and unlimited supply, since they are normally discarded. Furthermore, some bovine-ECM products have already been commercialized 28 and reportedly used without any safety issues which is promising for extending possible clinical applications.…”
mentioning
confidence: 99%
“…The gene IDH3A was in the peak SNP region on chromosome 21. The protein coded by IDH3A was up regulated in the ovaries of post-pubertal heifers as compared to pre-pubertal heifers [ 96 ]. The gene PTGDR was within a peak SNP region in this study and had been reported as a candidate in a previous GWAS as associated with age at first calving in cattle [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese Holstein cows, an SNP in the 5′ UTR region of FSHR is associated with superovulation [ 151 ]. The gene CS converts acetyl-CoA to citrate [ 152 ] which contributes to steroid synthesis downstream [ 96 ]. Steroidogenic genes CYP11A and HSD17B catalyze reactions of conversion of cholesterol to pregnanolone and estradiol-1 to estradiol-2, respectively [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using advanced proteomic technologies, Nguyen et al [ 157 ] and Tahir et al [ 158 ] identified differentially expressed proteins, their functions, and interactions in Brahman heifers. These authors showed that the puberty and fertility of these animals depended on proteins related to steroid synthesis and ovarian signaling pathways.…”
Section: The Genetics Of Heifers Sexual Precocitymentioning
confidence: 99%